2011
DOI: 10.1128/ec.05048-11
|View full text |Cite
|
Sign up to set email alerts
|

TbISWI Regulates Multiple Polymerase I (Pol I)-Transcribed Loci and Is Present at Pol II Transcription Boundaries in Trypanosoma brucei

Abstract: The unicellular eukaryote Trypanosoma brucei is unusual in having very little transcriptional control. The bulk of the T. brucei genome is constitutively transcribed by RNA polymerase II (Pol II) as extensive polycistronic transcription units. Exceptions to this rule include several RNA Pol I transcription units such as the VSG expression sites (ESs), which are mono-allelically expressed. TbISWI, a member of the SWI2/SNF2 related chromatin remodeling ATPases, plays a role in repression of Pol I-transcribed ESs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 68 publications
1
49
0
Order By: Relevance
“…Depletion of this factor increased the mRNA abundance of a reporter gene inserted promoter-proximally into a silent BES up to 60-fold, whereas only a fivefold increase of the corresponding silent VSG mRNA was observed. TbISWI was found to occupy the entire length of both silent and active BESs, but was not enriched at BES promoters (Stanne et al, 2011). Although the specific function of TbISWI remains to be determined, these results suggest that TbISWI controls RNAPI transcription elongation rather than initiation.…”
Section: Factors Involved In Bes Transcription Regulationmentioning
confidence: 99%
“…Depletion of this factor increased the mRNA abundance of a reporter gene inserted promoter-proximally into a silent BES up to 60-fold, whereas only a fivefold increase of the corresponding silent VSG mRNA was observed. TbISWI was found to occupy the entire length of both silent and active BESs, but was not enriched at BES promoters (Stanne et al, 2011). Although the specific function of TbISWI remains to be determined, these results suggest that TbISWI controls RNAPI transcription elongation rather than initiation.…”
Section: Factors Involved In Bes Transcription Regulationmentioning
confidence: 99%
“…This, along with recent results [39,40], strongly suggested the involvement of chromatin remodelling in the regulation of the transcriptional state of an ES. Indeed, the chromatin remodeller TbISWI was shown to play a role in repression of pol I transcribed ESs in both BF and PF stages of T. brucei [41]. TbISWI also contributed to the down regulation of PF-specific procyclin genes, non-transcribed VSG arrays and minichromosomes.…”
Section: Transcription In T Bruceimentioning
confidence: 99%
“…The active B-ES has very few nucleosomes while silent ESs are packed with nucleosomes (Figueiredo & Cross 2010;Stanne & Rudenko 2010). A number of studies also showed that chromatin remodeling plays an important role, particularly in regulating the B-ES promoter activity: Depletion of a Swi/Snf homolog, TbISWI, led to an elevated transcription from the silent ES promoters, although VSG expression is not affected (Hughes et al 2007;Stanne et al 2011); Deletion of the histone H3K79 methyltransferase TbDot1b led to a 10-fold increase in transcription throughout the silent ESs (Janzen et al 2006); Of the three T. brucei histone deacetylase homologs, DAC3 is required for B-ES promoter silencing at both BF and PF stages, and DAC1 antagonizes basal telomeric silencing in BF cells without affecting B-ES transcription (Wang et al 2010); And depletion of TbSpt16, a subunit of the FACT chromatin remodeling complex, also led to an ~20-fold increase in silent B-ES promoter transcription in both BF and PF cells (Denninger et al 2010). Third, ever since the discovery that VSGs are exclusively expressed from subtelomeric regions (de Lange & Borst 1982), it has been proposed that telomeres may play an important role in VSG expression regulation (Dreesen et al 2007).…”
Section: Rap1-mediated Silencing Is Essential For Monoallelic Expressmentioning
confidence: 99%